Abnormal Ulnar Variance: A New Perspective in Rheumatoid Arthritis-Related Joint Damage - Ketenci, Sertaç; Pekdiker, Mete; Uzuner, Bora; Durmuş, Dilek (Archives of Rheumatology, 2025)
Background/Aims: Rheumatoid arthritis (RA) is characterized by significant inflammation and joint damage. This study aims to investigate the frequency of abnormal ulnar variance (AUV) in RA patients and its associated factors. Materials and Methods: A total of 108 established RA patients meeting the 2010 ACR/EULAR RA criteria were included. After exclusions, the study proceeded with 98 patients. Demographic, laboratory, and clinical data were recorded. X-rays of the wrists were taken in accordance with the literature, with the forearm in a neutral rotation, the elbow flexed at 90°, the shoulder abducted at 90°, and ulnar variance was assessed with Hulten’s method. A displacement of 1 mm or more of the ulna relative to the radius was defined as AUV. Results: The average age was 58.11 ± 12.05 years, with 82% being female. The mean disease duration was 175.16 ± 100.5 months, and the average diagnostic delay was 16.4 ± 11.18 months. Abnormal ulnar variance was present in 47.9% of patients. In patients with AUV, the average UV for the right hand was +2.24 mm, while the average for the left hand was +2.40 mm. When considering all RA cases, the average UV was +1.06 mm for the right hand and +1.09 mm for the left hand. In the multivariate analysis, RA-type joint involvement (RJI) and severe joint involvement (SJI) were identified as independent predictors of AUV. Conclusion: This study suggests that AUV may be an important finding in established RA. Future larger-scale and prospective studies are needed to elucidate the significance of AUV in RA cases.